Pelatihan Pembelajaran Bahasa Inggris SD Ramah Anak - Nurhajati, Diani (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2020)
Teaching English to elementary school students must be prepared well in order to make the instruction successful. It must be taught by qualified English teachers who understand the characteristics of the students as well the appropriate teaching strategy. The teachers should understand that the process of teaching must be friendly child. It means that the materials are familiar with the students and they are in the level of their ability. The process of teaching must also suitable with their characteristics. Therefore, the English department lecturers of Nusantara PGRI Kediri University carried out a workshop for the elementary school English teachers at Kediri. The objective of the activity is to train the teachers so that they can apply in the classroom when they teach English for their students. The materials of the workshop covered the teacher’s attitude, how to develop the materials, and various teaching strategies. The teachers’ attitude is their expressions and body language when they interact with the students. They must leave the feeling of being teachers, but they merge as if they are children. The friendly child materials are the ones that the students are familiar. For examples, the topics are at their world, using simple expressions that are used in real context, and provided with media to support the context. Besides, they focus on more oral activities rather than written activities. Finally, the appropriate teaching strategies are songs, telling a story, and fun games.